Strike slip motion and the triggering of subduction initiation - Li, Yida; Gurnis, Michael (Frontiers in Earth Science, 2023)
Plate tectonic reconstructions of three of the best-defined Cenozoic subduction initiation(SI) events in the western Pacific, Izu-Bonin-Mariana, Vanuatu, and Puysegur subduction zones, show substantial components of strike-slip motion before and during the SI. Using computational models, we show that strike-slip motion has a large influence on the effective strength of incipient margins and the ease of SI. The parameter space associated with visco-elasto-plastic rheologies, plate weakening, and plate forces and kinematics is explored and we show that subduction initiates more easily with a higher force, a faster weakening, or greater strike-slip motion. With the analytical solution, we demonstrate that the effect of strike-slip motion can be equivalently represented by a modified weakening rate. Along transpressive margins, we show a block of oceanic crust can become trapped between a new thrust fault and the antecedent strike-slip fault and is consistent with structural reconstructions and gravity models of the Puysegur margin. Together, models and observations suggest that SI can be triggered when margins become progressively weakened to the point that the resisting forces become smaller than the driving forces, and as the negative buoyancy builds up, the intraplate stress eventually turns from compressional into extensional. The analytical formulation of the initiation time $t_{SI}$ marking the moment when intraplate stress flips sign, is validated with a few SI cases. The analytical solution shows that $t_{SI}$ is dominated by convergence velocity, while the plate age, strike-slip velocity, and weakening rate all have a smaller but still important effect on the time scale of SI.